Chromatographic and NMR analysis of lachemilla orbiculata in two ecuadorian andean localities [Análisis cromatográfico y RMN de lachemilla orbiculata en dos localidades de los andes ecuatorianos] - Malagon Aviles, O. (2017)
Traditional uses of plants for the treatment of diseases are attributed to the presence of secondary metabolites, such as the Rosaceae family characterized by containing tannin, sorbitol, triterpenes and steroids. Lachemilla, a genus of the Rosaceae, native and diverse in the Andean region, is used with medicinal and environmental purposes in Colombia and Ecuador. This study was done using leaves of Lachemilla orbiculata collected at two locations in the Ecuadorian Andes (Fierro Urco and Papallacta). A quantification of total phenols in the two localities revealed that in Fierro Urco L. orbiculata has 356.35 mg GAE/g and in Papallacta it has 368.8 mg GAE/g, which shows a considerable antioxidant capacity of the species. However, this result differs from a previous study made in Colombia by Argoti et al. (2011) in which they found approximately half of the quantity reported in this study. This difference could be explained by climate conditions, soil status, and other environmental factors. Furthermore, the most abundant terpene isolated in each locality, 25.9 mg in Fierro Urco and 6.9 mg in Papallacta, was identified through analysis of Nuclear Magnetic Resonance: 1H, 13C and DEPT, as stigmasterol, a sterol reported for the first time in the genus Lachemilla.